A Systematic Review and Synthesis of Psychometric Properties of the Numeric Pain Rating Scale and the Visual Analog Scale for Use in People With Neck Pain. Issue 2 (26th October 2021) - Modarresi, Shirin; Lukacs, Michael J.; Ghodrati, Maryam; Salim, Shahan; MacDermid, Joy C.; Walton, David M.
Abstract : Objectives: To conduct a systematic search and synthesis of evidence about the measurement properties of the Numeric Pain Rating Scale (NPRS) and the Visual Analog Scale (VAS) as patient-reported outcome measures in neck pain research. Methods and Materials: CINAHL, Embase, PsychInfo, and MedLine databases were searched to identify studies evaluating the psychometric properties of the NPRS and the VAS used in samples of which >50% of participants were people with neck pain. Quality and consistency of findings were synthesized to arrive at recommendations. Results: A total of 46 manuscripts were included. Syntheses indicated high-to-moderate-quality evidence of good-to-excellent (intraclass correlation coefficient 0.58 to 0.93) test-retest reliability over an interval of 7 hours to 4 weeks. Moderate evidence of a clinically important difference of 1.5 to 2.5 points was found, while minimum detectable change ranged from 2.6 to 4.1 points. Moderate evidence of a moderate association ( r =0.48 to 0.54) between the NPRS or VAS and the Neck Disability Index. Findings from other patient-reported outcomes indicated stronger associations with ratings of physical function than emotional status. There is limited research addressing the extent that these measures reflect outcomes that are important to patients. Discussion: It is clear NPRS and the VAS ratings are feasible to implement, provide reliable scores and relate to multi-item patient-reported outcome measures. Responsiveness (meaningful change) of the scales and interpretation of change scores requires further refinement. The NPRS can be a useful single-item assessment complimenting more comprehensive multi-item patient-reported outcome measures in neck pain research and practice.